A companion to the Reformation world - Hsia, Ronnie Po-chia; (1955-...) (U.S.A., 2004)
Features essays that provide an overview of work in Reformation history. These articles present the Catholic Renewal as a continuum of the Protestant Reformation and focus on the workings of religious reform in various areas of Latin Christendom. This book is useful to students and professional historians.
Keywords: Reformation (Christianity)